The Antitumor Activity and Mechanism of a Natural Diterpenoid From Casearia graveolens - Li, Ying; Ma, Jun; Song, Ziteng; Zhao, Yinan; Zhang, Han; Li, Yeling; Xu, Jing; Guo, Yuanqiang (Frontiers in Oncology, 2021)
Casearlucin A, a diterpenoid obtained from Casearia graveolens, has been reported to possess strong cytotoxic activity. However, the in vivo anti-tumor effects and the action mechanism of casearlucin A remain poorly understood. Our study revealed that casearlucin A arrested cell cycle at G0/G1 stage and induced cell apoptosis in cell level. Additionally, casearlucin A inhibited HepG2 cell migration via regulating a few of metastasis-related proteins. Furthermore, it inhibited tumor angiogenesis in zebrafish in vivo. More importantly, casearlucin A significantly inhibited cell proliferation and migration in an in vivo zebrafish xenograft model. Collectively, these results are valuable for the further development and application of casearlucin A as an anticancer agent.